Planning physical preparation of student volleyball players for club competitions using the BIODEX platform - Kazakov, D.N. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a methodology for planning physical preparation of student volleyball players for club competitions using the BIODEX platform. Methods and structure of the study. The study was conducted at the MSU sports complex from September to December 2023. It involved 28 student volleyball players aged 18-23, with qualifications of no lower than first rank and 5-9 years of experience. Participants were randomly assigned to control and experimental groups of 14 persons each, comparable in anthropometric indicators. The control group followed the standard programme including three court training sessions and two gym sessions per week. In the experimental group, one gym session was replaced with training on the BIODEX SYSTEM PRO-4 platform, conducted twice a week for 30 minutes. Results and conclusions. Application of the BIODEX platform proved more effective than the standard preparation programme. The proposed methodology can be used in the preparatory period when preparing student volleyball players for club competitions.